2017
DOI: 10.1002/hep4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and the ongoing role of liver biopsy evaluation

Abstract: Nonalcoholic fatty liver disease (NAFLD) is one of the most common underlying causes of chronically elevated liver tests and liver disease in adults and children worldwide and may be strongly suspected if not diagnosed by ever evolving and available serologic and imaging‐based noninvasive tests. However, the definitive diagnosis of the most progressive form of NAFLD, nonalcoholic steatohepatitis, and the identification of fibrosis stage still require liver biopsy evaluation as noninvasive testing has not repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 63 publications
1
47
0
1
Order By: Relevance
“…Evidence suggests that fibrosis can progress but it may also regress during the disease course of NAFLD . Considering the biochemically stable nature of elastin compared with collagen, elastin accumulation in the liver may contribute to the irreversibility of the disease.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Evidence suggests that fibrosis can progress but it may also regress during the disease course of NAFLD . Considering the biochemically stable nature of elastin compared with collagen, elastin accumulation in the liver may contribute to the irreversibility of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…(9,43,44) Previous evidence has shown that advanced fibrosis is associated with increased risk of all-cause and liver-related mortality. (10,45) Intriguingly, our quantitative analysis did not show any significant differences in fiber area ratios between stages 2 and 3. A histologic difference between the two stages is the presence or absence of bridging fibrosis.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Classical pathological staging systems have no stage beyond F4; however, it appears that fibrosis progresses and parenchymal remodeling continues even within the final fibrotic stage F4 . Furthermore, fibrosis not only progresses but may also regress during the disease course . These results indicate that an accurate assessment of fibrosis using quantitative computational fiber measurements combined with the classical pathological grading of structural changes might be able to predict more precisely the outcomes in patients with NAFLD.…”
Section: Assessment Of Liver Fibrosismentioning
confidence: 91%